THE IMPACT OF THE BOYCOTT OF ISRAELI PRODUCTS, BRANDS AND THEIR SUPPORTERS ON THE INDONESIAN ECONOMY - Santosa, Sinta Dewi Laksmi (EP FEB UNS, 2024)
This study examines the impact of the boycott on the Indonesian economy, focusing specifically on key sectors affected and the broader economic implications. Using a qualitative approach, this research employs literature studies as the primary data collection method. The findings indicate that the boycott has significantly boosted the consumption and production of local products in Indonesia, particularly in the food and textile industries. This increase in local production has the potential to absorb a larger workforce, thereby reducing unemployment. Furthermore, the study highlights the importance of improving the quality of local products and emphasizes the need for continued government support. With these measures, Indonesia’s local products could not only strengthen the domestic economy but also enhance their competitiveness on the international stage.